Optimasi Media Sosial dalam Digital Marketing untuk Meningkatkan Brand Awareness dan Interaksi Konsumen - Cantika Aura Jahzy; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research purpose is to investigate and analyze social media optimization strategies in the context of digital marketing to increase brand awareness and consumer interaction. The research method used is a qualitative approach with a case study approach to gain an in-depth understanding of effective practices in social media optimization. Data was collected through in-depth interviews with digital marketing practitioners, participatory observation, and social media content analysis.